Analisis Faktor Yang Mempengaruhi Kinerja Usaha Mikro Kecil dan Menengah (UMKM) Kota Tebing Tinggi - Mirwansyah Putra Ritonga; Komala Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The development of Small and Medium Enterprises (SMEs) is one of the government's priorities, especially in Tebing Tinggi City. Known as an industrial city, it becomes an opportunity for the development of SMEs, which are the majority of the workers. The development of SMEs, especially